FINANCIAL WELL-BEING OF CIVIL SERVANT IN INDONESIA: THE ROLE OF FINANCIAL BEHAVIOR - Elimar Sinaga; Khaira Amalia Fachrudin; Syahyunan (CV. Radja Publika, 2024)
Financial well-being is an important part that individuals must achieve to improve the quality of life and performance in the organization. For organizations, financial well-being can increase a positive brand image and create trust and then at the macro level, financial well-being is very important for sustainable development goals. However, achieving financial well-being is still a challenge for both the government and organizational leaders. The aim of this research is to analyze the factors that influence financial well-being through financial behavior of civil servants in one organizational unit in Indonesia. This research examined 240 civil servants in one organizational unit in Indonesia who were selected using Proportionate Stratified Random Sampling techniques and tested using the PLS SEM statistical analysis method. This research uses a confidence level of 95%, ???? = 5%. The research results show that financial literacy factors and attitudes towards money have a positive and significant impact on financial well-being. Meanwhile, internal locus of control has an insignificant positive impact on financial well-being and financial socialization has an insignificant negative impact on financial well-being. The factors of financial literacy, internal locus of control, and financial socialization have a positive and significant effect on financial behavior. Meanwhile, attitudes towards money have an insignificant positive impact on financial behavior. Financial behavior successfully mediates the influence of financial literacy, internal locus of control, and financial socialization on financial well-being. However, financial behavior did not succeed in mediating the influence of attitudes towards money on financial well-being.